2016
DOI: 10.1155/2016/3092828
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Four‐Week Multivitamin Supplementation on Mood in Healthy Older Women: A Randomized Controlled Trial

Abstract: Objective. Nutritional deficiencies have been associated with cognitive decline and mood disturbances. Vitamin intake can influence mood and randomized controlled trials have demonstrated that multivitamin supplements are capable of reducing mild symptoms of mood dysfunction. However, few studies have focussed on healthy older women. Methods. This study investigated the effects of four weeks' multivitamin supplementation on mood in 76 healthy women aged 50–75 years. Mood was assessed before and after intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Seven studies included three to four other constituents, with the remaining containing a higher number of micronutrients or botanical constituents. The largest amount of other constituents came from Macpherson, et al [49], with a total of 37 additional constituents.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies included three to four other constituents, with the remaining containing a higher number of micronutrients or botanical constituents. The largest amount of other constituents came from Macpherson, et al [49], with a total of 37 additional constituents.…”
Section: Resultsmentioning
confidence: 99%
“…But the NBS supplement is processed from whole grain wheat enriched with broad spectrum micronutrients. A double-blind randomized controlled trial Macpherson et al also administered multivitamins to healthy females for four weeks and reported no significant improvement in symptoms of depression, anxiety or stress (Macpherson et al, 2016). They included women with a different age group (50-75 year old).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the relationship between a healthy diet and individual nutrients and their impact on depression, such as fatty acids, vitamins, and minerals [ 12 14 ]. Moreover, intervention studies using supplements that include several nutrients, such as multivitamins, have examined the overall effect on patient mood [ 15 17 ]. In particular, increased fruit and vegetable intake has been widely associated with a better psychological and health status and a decrease in the likelihood of depressive symptoms [ 9 – 11 , 18 ], while other studies revealed that the association is insignificant [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%